DETERMINANTS OF SHADOW BANKING GROWTH – EVIDENCE FROM CEE COUNTRIES - Naumovska, Elena; Peovska, S.; Jovanovski, Kiril; Cvetkoska, Violeta (Publishing India, 2023)
The focus of this paper is placed on shadow banking as a less regulated segment of the financial system recognizable by its increasingly significant presence in the countries of Central and Eastern Europe with a tendency of further accelerated growth in recent years. Despite the significant contribution by providing alternative sources of liquidity and alternative funding to the real economy, shadow banking can be a significant source of systemic risk. The subject of this paper is to examine the relationship between selected macroeconomic and financial variables and the size of the shadow banking system by applying the regression with time fixed effects with fixed effects in seven Central and Eastern European countries over the period 2007-2021 with a quarterly dataset. Empirical results confirm that shadow banking positively correlates with traditional banks, complementing the demand for financial products that the banking sector, adhering to strict regulatory requirements, abstains from supporting. Our study aims to highlight the threat, more excellent orientation towards strengthening the bank’s capital requirements to cause further expansion of the activities in the non-banking part of the financial sector beyond the sight of the regulators, as well as the necessity to identify the challenge of making this less regulated part of the financial system more stable and sustainable.
Keywords: shadow banking, banking sector, regulatory requirements, systemic risk